Skládání přísahy v kontextu romského soudu - Marušiaková, Elena; Popov, Veselin (Romano džaniben, 2011)
Common objects connected to different religious cults bear constant sacrality which is not lost in time and space. At the same time there are objects of everyday use which can materialize specific meanings, ideologies and relationships and may be turned into sacred objects, their meaning thus can change in time and space. The article discusses and explores the notion of constant and temporary sacrality in ethnographic contexts of Romani court on the example of several Roma groups from Central, Eastern and South Eastern Europe. During the seating of the Roma court, when there is a lack of evidence for an argument to be settled, the last resort is used – the case is “decided by God”: ritualized oath is taken over sacral objects, most often a cross or an icon. Among some communities, however, the oath is taken over specific objects of everyday use which - in the context of the ritual - receive temporary sacral meaning. The article discusses as well the significance of the oath for preservation of unity in Roma groups.